Effect of top-dressed potassium fertilization on the yield and quality of cucumber - Correa, Carla Veronica [UNESP]; Sousa Gouveia, Aline Mendes de [UNESP]; Menezes Martins, Bruno Novaes [UNESP]; Brito Lima Lanna, Natalia de [UNESP]; Barbosa Tavares, Ana Emilia [UNESP]; Mendonca, Veridiana Zocoler [UNESP]; Jorge, Leticia Galhardo [UNESP]; Inacio Cardoso, Antonio Ismael [UNESP]; Evangelista, Regina Marta [UNESP] (Taylor & Francis Inc, 2018)
The current study aimed to evaluate the effect of top-dressed potassium (K) application on the production of hybrid cucumber Sapphire. The experimental design was a randomized complete block, with five blocks of 0.80 x 0.40m(2) each and eight replicate plants per block. The five fertilization rates of K used were 0, 45, 90, 135, and 180kg K2O ha(-1). Data collection consisted of the estimation of fruit diameter, fruits length, fruit fresh and dry weights, the number of fruits per plant, and the weight of fruits per plant. The number of fruits per hectare and the fruit fresh weight per hectare were calculated. Fruit tissue was analyzed for determination of macronutrient concentrations, pH, titratable acidity, soluble solids, sugar contents, and protein content. The data were statistically analyzed using regression analysis and analysis of variance (ANOVA). There was a significant effect of the fertilization rate of K on fruit diameter, fruit fresh and dry weights, macronutrients concentrations in fruits, titratable acidity, soluble solids, and reducing sugars. A quadratic equation was adjusted for the number of fruits per plant and per hectare; fruit yield per plant and per hectare, with maximum top-dressing doses, was estimated to be between 60 and 95kg K2O ha(-1). A linear increase was obtained in the pH. An increase in the K fertilization rate caused a linear decrease in the fruit length.
Keywords: Cucumis sativus; fertilizer; macronutrient; postharvest productivity